Estimating expected life-years and risk factor associations with mortality in Finland: cohort study - Tommi Härkänen; Seppo Koskinen; Paul Knekt; Laura Sares-Jäske; Pekka Jousilahti; Markku Peltonen (BMJ Open)
Objective To develop a tool to inform individuals and general practitioners about benefits of lifestyle changes by providing estimates of the expected age of death (EAD) for different risk factor values, and for those who plan and decide on preventive activities and health services at population level, to calculate potential need for these.Design Prospective cohort study to estimate EAD using a model with 27 established risk factors, categorised into four groups: (1) sociodemographic background and medical history, (2) lifestyles, (3) life satisfaction, and (4) biological risk factors. We apply a Poisson regression model on the survival data split into 1-year intervals.Participants Total of 38 549 participants aged 25–74 years at baseline of the National FINRISK Study between 1987 and 2007.Primary outcome measures Register-based comprehensive mortality data from 1987 to 2014 with an average follow-up time of 16 years and 4310 deaths.Results Almost all risk factors included in the model were statistically significantly associated with death. The largest influence on the EAD appeared to be a current heavy smoker versus a never smoker as the EAD for a 30-year-old man decreased from 86.8 years, which corresponds to the reference values of the risk factors, to 80.2 years. Diabetes decreased EAD by >6.6 years. Whole or full milk consumers had 3.4 years lower EAD compared with those consuming skimmed milk. Physically inactive men had 2.4 years lower EAD than those with high activity. Men who found their life almost unbearable due to stress had 2.8 years lower EAD.Conclusions The biological risk factors and lifestyles, and the factors connected with life satisfaction were clearly associated with EAD. Our model for estimating a person’s EAD can be used to motivate lifestyle changes.